Red Dirt Thinking on Child Wellbeing in Indigenous, Rural and Remote Australian Communities: The SpICE Model “I just don’t want my kid to struggle like I did at school” - Clarke, Kendall; Denton, Marijke (The Australian Journal of Indigenous Education, 2013)
Supporting children in their early development and learning has long-term benefits for both them and the broader community. Yet in Australia we still have significant examples of inequality of opportunity (Allan, 2010) and other structural barriers to family wellbeing, particularly in Indigenous and rural and remote communities (Bourke, Humphreys, Wakerman, & Taylor, 2012). One of the structural barriers is the frequently siloed approach to addressing issues around child wellbeing and learning, when a collaborative effort results in more effective and sustainable outcomes. Red Dirt (Indigenous, rural and remote) communities are fertile ground for the emergence of partnership models that provide solutions to perennial, complex community issues and siloed service provision that impact on learning outcomes. The aim of this article is to provide a background and commentary to contribute to the discussion about what works to promote child wellbeing in Australia and put forward the SpICE Model as part of the solution. Drawing on a body of literature and experiences in the field, this article will introduce a model for collaboration that should contribute to child wellbeing: the Specialist Integrated Community Engagement (SpICE) Model. First, we give an overview of the context of adversity as it specifically relates to educational outcomes for children. The principles underpinning the SpICE Model, on how to harness opportunity from adversity, are also described as they provide insight into how to achieve sustainable change in this context. In conclusion, some of the potential challenges of embedding SpICE into practice are discussed. The argument developed throughout this article is that the SpICE Model has currency for a wide range of education, health, disability and welfare collaborations and how they impact on child, family and community wellbeing.